3
$\begingroup$

$a_1,\:b_1>0$

$a_{n+1}=\frac{a_n+b_n}{2},\:b_{n+1}=\sqrt{a_n\cdot b_n}$

The question asks to prove that: $\lim _{n\to \infty }\left(a_n\right)=\lim \:_{n\to \:\infty \:}\left(b_n\right)$.

Proving it once I show that both sequences converge is obviously the easy part. However, I can't get to that point.

$\endgroup$
4
$\begingroup$

By the AM-GM inequality we have: $$ b_n \leq b_{n+1} \leq \ldots \leq a_{n+1}\leq a_n $$ so both the sequences $\{a_n\}_{n\in\mathbb{N}}$ and $\{b_n\}_{n\in\mathbb{N}}$ are converging since they are monotonic and bounded. Since: $$ a_{n+1}-b_{n+1} = \frac{1}{2}(\sqrt{a_n}-\sqrt{b_n})^2 \leq \frac{1}{2}(a_n-b_n)$$ the limit is the same.

$\endgroup$
4
$\begingroup$

Try using the AMGM inequality: if $c,d>0$ then: $$ \frac{c+d}{2}\ge \sqrt{cd} $$

More specifically - Notice that we have the following inequalities for all $n\ge 1$:

  1. $a_n \ge b_n$ (AMGM inequality)
  2. $a_{n+1} \le a_n$ (by the previous inequality and the definition of $a_n$)
  3. $b_{n+1} \ge b_{n}$ (by the first inequality and the definition of $b_n$)

This implies that $(a_n)$ is nonincreasing and bounded from below by $b_1$ (use 1 and 3) and that $(b_n)$ is nondecreasing and bounded from above by $a_1$ (use 1 and 2), thus both converge.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.